La fin d’une école, le début d’une autre ? - François Durpaire; jean-louis Durpaire (Éducation et Socialisation)
Our research was aimed at understanding the significance of terms used in educational institutions and official documents : resource/learning centers, classrooms, school environment to education stakeholders. We interviewed year heads, school/teachers librarians as well as managerial staff members on their thoughts of these school learning environments, their importance, the ways in which they can be improved and their prospective visions for the entire educational structure